The Approximation Aspects of Characteristics of Semiconductor Temperature Sensors - Dumcius, A.; Augutis, V.; Gailius, D. (Elektronika ir Elektrotechnika, 2011)
The aim of the work is to analyze the possibilities to reduce the temperature measurement errors which emerge when using semiconductor analogous and digital sensors and thermistor-based sensors. The dependence of the output signal of the semiconductor temperature sensors in respect of the temperature is non-linear. By using the additional calibration at the several reference temperature points the sensor output signal dependencies on the temperature can be linearized better. In this way it is possible to reduce the temperature measurement errors several times and/or expand the range of the measured temperatures without the use of the expensive and precise temperature sensors. It was shown that for the sensors type DS620 the errors after the additional linearization and correction in the range (20-90) 0C did not exceed ±0.035 0C. The experimental and calculation results are provided. Ill. 8, bibl. 11, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.443